A REVIEW ON THE NEURAL CIRCUITS IN ANXIETY DISORDERS - Arya, Ashwani; Sindhwani, Gulshan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Anxiety disorders are among the most common mental, emotional, and behavioral problems. These affect one-eighth of the total population worldwide. Anxiety disorders are a group of mental disorders characterized by irritability, fear, insomnia, nervousness, tachycardia, inability to concentrate, poor coping skills, palpitation, sweating, agoraphobia, and social withdrawal. Brain regions and networks involved in anxiety symptomatology is an effort to better understand the mechanism involved and to develop more effective treatments for the anxiety disorders. Thus, neuroanatomical and neuroimaging research in anxiety disorders has centered on the role of the amygdala, reciprocal connections between the amygdala and the prefrontal cortex, and, most recently, alterations in interoceptive processing by the anterior insula. Anxiety disorders are characterized by alterations in a diverse range of neurochemical systems, suggesting ample novel targets for drug therapies. The neurotransmitter like corticotropin-releasing factor, neuropeptides (substance P, neuropeptide Y, oxytocin, orexin, and galanin) are implicated in anxiety pathways. Each of these active areas of research holds promise for expanding and improving evidence-based treatment options for individuals suffering with clinical anxiety. Therefore, this article gives the information on the neurocognitive mechanisms, causes, neurotransmitter involved in anxiety disorders and emphasize on the therapeutic targets for anxiety disorders. Keywords: Anxiety, Stress, Amygdala, Corticotropin releasing factor, Insula, Thalamus.